Emergency aortic arch replacement using the debranch‐first technique with a custom‐made prosthesis. Issue 1 (15th October 2019) - Belluschi, Igor; Verzini, Alessandro; Bertoglio, Luca; Castiglioni, Alessandro
Abstract: Acute aortic arch dissections represent life‐threatening conditions with a high rate of mortality and neurological complications. Past longer techniques included an "en bloc" replacement of epiaortic vessels or the frozen elephant trunk (FET) procedure with conventional grafts for chronic dilatation. In this report, we described a case of an acute aortic dissection in a patient with aberrant right subclavian artery and challenging sovra‐aortic vessel anatomy, treated with the new custom‐made E‐Vita Open Plus FET graft.